Técnica maitland versus técnica mulligan en la movilidad de rodilla en pacientes varones de 25 a 40 años, con plastia de ligamento cruzado anterior, en el Hospital Básico 11 B.C.B. “Galápagos”. Periodo Septiembre-Diciembre 2024. - Aguaguiña Rosillo, Anthony Sebastian (2025)
The purpose of this research was to compare the therapeutic effects of the Mulligan Technique and the Maitland Technique in the male population with limited mobility in the knee, specifically in active extension, after anterior cruciate ligament plasty. A quantitative approach with a longitudinal cohort experimental design was used, and the sample consisted of 24 men between 25 and 40 years of age, who met the established inclusion criteria. The intervention protocol contemplated the application of both physiotherapeutic techniques three times a week, for six consecutive weeks, with ten-minute sessions per technique applied. The Maitland Technique was applied by means of passive oscillatory movements of flexion and extension with grade III mobility, aimed at restoring knee joint amplitude. In contrast, the Mulligan Technique focused on combined joint movements, specifically a posterior glide followed by an anterior glide over the knee joint line, seeking to facilitate active movement without pain. Joint mobility assessments were performed using the G Pro goniometric test, an instrument that accurately quantified active knee extension. The findings revealed that the Maitland Technique produced more significant improvements in the range of motion of active knee extension compared to the G Pro Goniometric Test.